2018
DOI: 10.1002/adem.201701057
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Al25 − xCr25 + 0.5xFe25Ni25 + 0.5x (x = 19, 17, 15 at%) Multi‐Component Alloys

Abstract: A series of Al25 − xCr25 + 0.5xFe25Ni25 + 0.5x (x = 19, 17, 15 at%) multi‐component alloys are prepared by arc‐melting and rapid solidification of copper molds. The technique of thermal‐mechanical processing is further applied to the master alloys to improve their mechanical properties. These alloys consist of face‐centered cubic (FCC) and body‐centered cubic (BCC) structure. The volume fraction of the BCC phase increases as Al content increase and Cr and Ni contents decrease, accompanied with a microstructura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The mass fraction of crystalline water is approximately 46%, much higher than that of an ordinary inorganic salt. The internal of high water material is network structure, which is ideal for moisture storage 13 . The typical branch network structure of high water material is shown in Figure 2.…”
Section: Specimen Preparation and Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass fraction of crystalline water is approximately 46%, much higher than that of an ordinary inorganic salt. The internal of high water material is network structure, which is ideal for moisture storage 13 . The typical branch network structure of high water material is shown in Figure 2.…”
Section: Specimen Preparation and Test Methodsmentioning
confidence: 99%
“…Sun et al 6 found that the high water material had the characteristics of quick setting and early strength; Feng et al 7 developed a new type of ultra‐high water material through a lot of experiments. The water content was further improved, but its mechanical properties were not significantly affected; Zhou et al 8 studied the strength deterioration of high water content materials under weathering conditions, the results showed that the durability of high water content materials was closely related to the environmental humidity; Wu et al 9 added fly ash and silica fume to the high water material, and obtained the effect of these two additives on the macro‐mechanical properties of the high‐water material, which would help reduce the filling cost for larger‐scale application; Sun et al 10–11 believed that the characteristics of ultra‐high water material, such as, strong plasticity and strength regeneration, were very suitable for underground filling and gave the load strength suitable for ultra‐high water material; Zhang et al 12 studied the post‐peak mechanical characteristics of the high‐water material for backfilling the gob‐side entry retaining; Li et al 13 studied the mechanical properties and damage constitutive model of high water materials at different loading rates, and obtained useful conclusions. It can be seen that the previous studies mainly focused on the instantaneous mechanical properties of high water material, while the long‐term mechanical properties were relatively less.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the NiFeCoCrCu HEA film underwent a phase transition from ductile FCC to hard BCC under ion radiation, and the presence of this mixed-phase structure achieved strong strain-hardening capabilities and large tensile ductility [39]. Therefore, the formation of mixing phases overcomes the strengthductility trade-off and further optimizes the properties of HEAs, making phase engineering a hotspot of current research [40][41][42].…”
Section: Mixed-phases Heasmentioning
confidence: 99%